Conectando capacidades na cadeia de suprimentos verde: a influência da teoria da colaboração no setor de plásticos no sul do Brasil - Soares, Isabel Teresinha Dutra (2018)
Given the relevance of collaboration for sustainable operations in the supply chain, and the pertinence of Supply Chain Capabilities (SCCs) as foundations for company competitive advantage, the aim of this study is to investigate the specific role of Supply Chain Capabilities (SCCs) in the implementation of green operations strategies and verify if the relationship between SCCs is mediated by the Active Engagement in Collaboration (AEC). A descriptive and exploratory field research was conducted. The research tool was applied to managers of companies in the plastic products sector, obtaining answers from 54 senior executives from South of Brazil. The data were treated by descriptive statistics, factorial analysis and structural equation modeling. The findings demonstrated that the successful implementation of sustainable/green operations strategies maintains a positive relationship with specific capabilities related to logistics/supply chain management. The AEC moderated the external integration, skills/knowledge and flexibility as capabilities in the supply chain management of the plastics sector. It was possible to observe that companies are cooperating with suppliers in operations of green purchasing as well as that they are implementing the design of products for reuse, recycling and recovery of materials, parts and components. Less consistent with the reality of the companies was the capability of internal integration, which reveals that the companies investigated are facing internally obstacles in collaborating to implement green manufacturing. This study is unprecedented and one of its contributions is to contain a robust review of international literature. The originality and the value of the study is also due to its application in the plastic products sector, a relevant sector to help modern life, but a sector that causes undeniable damage to the environment. The limitations of the study reside mainly in the size of the sample, which can be extended in future studies, as well as in the future the strategic areas of green operations may be expanded beyond design, purchasing and manufacturing.